Electroencephalogram Correlates the Role of Ashwagandha in Sleep and Memory Promoting Effect - Basani, Mounika; Malothu, Ramesh; Sinha, Rakesh Kumar; Murthy, Sindgi Vasudeva (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Ashwagandha (Withania somnifera), a known traditional medicine used in Ayurveda system of medicine, native to the India. Poor quality sleep always looked as serious complaint as it disrupts sleep. The natural phytoconstituents present in the ashwagandha believed to be adaptogen that helps the body to adapt stress by normalizing or correcting through balancing immune and neuroendocrine system. The mechanism that enhances sleep quality in the presence of ashwagandha is still unknown. Based on all available studies we investigated the effects of hydroalcoholic extract of ashwagandha effects on various bands of the electroencephalogram (EEG) to ascertain its role in behavior and sleep in rats. Material and methods: The present study explored in Wistar rats of either sex (n=12) used to record EEG in the presence of ashwagandha extracts (25mg/kg body weight). The previous studies revealed sleep promoting character of GABA very well documented in governing sleep and Withania somnifera known to posses mild to moderate hypnotic activity. We used conventional model for quantifying EEG in presence of ashwagandha extract and investigated its possible role in memory, behavior and sleep. Withania somnifera extract administered orally (25mg/ kg) for electrophysiological recordings. Comparison made between post administration of extract with baseline recording employing vehicle and is considered as control. The changes in various bands of EEG noticed following administration of ashwagandha extract. Results: The Withania somnifera extract increased electrophysiological properties in delta (p<0.001) and gamma (p<0.003) bands and was found to be statistically significant. Statistically significant changes not observed in theta and alpha band power but beta band power was reduced in its influence (p<0.013). Conclusion: The present study revealed enhanced activity of the slow wave in presence of ashwagandha extract and divulged the details of its role in sleep and memory.
Keywords: Ashwagandha; Data acquisition; Delta; Memory; Sleep; Frequency